1971
DOI: 10.1172/jci106667
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Glomerular Ultrafiltration in the Rat

Abstract: A B ST R A CT Using a unique strain of \VNistar rats endowed with glomeruli situated directly on the renal cortical surface, we measured glomerular capillary pressures using servo-nulling micropipette transducer techniques. Pressures in 12 glomerular capillaries from 7 rats averaged 60 cm H20, or approximately 50% of mean systemic arterial values. Wave form characteristics for these glomerular capillaries were found to be remarkably similar to those of the central aorta. From similarly direct estimates of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
105
3
1

Year Published

1973
1973
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(126 citation statements)
references
References 15 publications
17
105
3
1
Order By: Relevance
“…It is well documented that a close relationship exists between RPF and GFR, and that RPF is one of the major determinants of GFR, as reviewed by Brenner and Humes [12]. Our study also revealed a close relationship between these two variables (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…It is well documented that a close relationship exists between RPF and GFR, and that RPF is one of the major determinants of GFR, as reviewed by Brenner and Humes [12]. Our study also revealed a close relationship between these two variables (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…The mean sngfr was 52.7±2.9 nl/min/g kidney wt in the control plasma-expanded condition and fell to 24.4±1.9 nl/min g kidney wt (n = 7) (P < 0.001) after infusion of AGBM Ab ( Fig. 1 and Table II).…”
Section: Introductionmentioning
confidence: 89%
“…A value for the glomerular permeability coefficient (LpA) is also generated by this method (sngfr = LpA -EFP). At filtration pressure equilibrium (WrE -AP) as has been demonstrated for the hydropenic MunichWistar rat (11,17,24), a specific numerical value for LpA and EFP cannot be defined, but rather only a minimal and maximal possible value, respectively. However, at higher rates of rpf, produced by isoncotic plasma volume expansion in this study, the efferent EFP becomes significantly positive, or AP greatly exceeds 7rE.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its effect on efferent arteriolar resistance, Ang II has a marked influence on glomerular mesangial tone. Ang II promotes mesangial cell contraction and thus a decrease in the glomerular capillary ultrafiltration coefficient (Kf) (30,31). The Kf-lowering effect of Ang II is attenuated by the stimulatory effect of Ang II on the production of vasodilatory prostaglandins (32).…”
Section: Renal Actions Of Angiotensin IImentioning
confidence: 99%